Multiwalled carbon nanotubes (MWCNTs) as solid phase extractor (SPE) for the determination of lead in water samples - Farhanah Azwanee Mohd. Ali Chooi, 1987-; Zaiton Abdul Majid, supervisor; Jafariah Jaafar; Fakulti Sains (2009)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2009